2013
DOI: 10.1371/journal.pone.0064515
|View full text |Cite
|
Sign up to set email alerts
|

The Independent Acquisition of Plant Root Nitrogen-Fixing Symbiosis in Fabids Recruited the Same Genetic Pathway for Nodule Organogenesis

Abstract: Only species belonging to the Fabid clade, limited to four classes and ten families of Angiosperms, are able to form nitrogen-fixing root nodule symbioses (RNS) with soil bacteria. This concerns plants of the legume family (Fabaceae) and Parasponia (Cannabaceae) associated with the Gram-negative proteobacteria collectively called rhizobia and actinorhizal plants associated with the Gram-positive actinomycetes of the genus Frankia. Calcium and calmodulin-dependent protein kinase (CCaMK) is a key component of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 50 publications
4
51
0
Order By: Relevance
“…Similar symbiotic cascade requirements were also found in the actinorhizal plant C. glauca, in which both SYMRK (Gherbi et al, 2008) and CCaMK (Svistoonoff et al, 2013) were shown to be required for nodulation. It is noteworthy that a microorganism lacking nod genes activates such a signaling pathway.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Similar symbiotic cascade requirements were also found in the actinorhizal plant C. glauca, in which both SYMRK (Gherbi et al, 2008) and CCaMK (Svistoonoff et al, 2013) were shown to be required for nodulation. It is noteworthy that a microorganism lacking nod genes activates such a signaling pathway.…”
Section: Discussionsupporting
confidence: 61%
“…The symbiotic calcium-and calmodulin-dependent protein kinase CCaMK is required for the interpretation of this Ca 2+ signature (Oldroyd and Downie, 2006;Madsen et al, 2010;Singh et al, 2014). Mutations in CCaMK or CCaMK RNAi prevent root infections by microsymbionts through the inhibition of either the formation of ITs or the endocytosis of rhizobia inside the nodules, and they block or, in the case of RNAi lines, reduce nodule organogenesis in legumes (Catoira et al, 2000;Lévy et al, 2004;Mitra et al, 2004;Capoen et al, 2009;Sinharoy and DasGupta, 2009) and actinorhizal plants (Svistoonoff et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nature of the nodulation signal(s) emitted by Frankia spp. is still unknown, but it has been shown that its perception depends on the common Nod signaling pathway (Gherbi et al, 2008;Svistoonoff et al, 2013). In the actinorhizal tree Casuarina glauca, the involvement of the phytohormone auxin in symbiotic signaling in plant cells infected by Frankia spp.…”
mentioning
confidence: 99%